Can conservation tillage reduce N2O emissions on cropland transitioning to organic vegetable production? - Chen, Guihua; Kolb, Lauren; Cavigelli, Michel A.; Weil, Ray R.; Hooks, Cerruti R.R. (The Science of the total environment, 2018)
Nitrous oxide (N2O) is an important greenhouse gas and a catalyst of stratospheric ozone decay. Agricultural soils are the source of 75% of anthropogenic N2O emissions globally. Recently, significant attention has been directed at examining effects of conservation tillage on carbon sequestration in agricultural systems. However, limited knowledge is available regarding how these practices impact N2O emissions, especially for organic vegetable production systems. In this context, a three-year study was conducted in a well-drained sandy loam field transitioning to organic vegetable production in the Mid-Atlantic coastal plain of USA to investigate impacts of conservation tillage [strip till (ST) and no-till (NT)] and conventional tillage (CT) [with black plastic mulch (CT-BP) and bare-ground (CT-BG)] on N2O emissions. Each year, a winter cover crop mixture (forage radish: Raphanus sativus var. longipinnatus, crimson clover: Trifolium incarnatum L., and rye: Secale cereale L.) was grown and flail-mowed in the spring. Nearly 80% of annual N2O-nitrogen (N) emissions occurred during the vegetable growing season for all treatments. Annual N2O-N emissions were greater in CT-BP than in ST and NT, and greater in CT-BG than in NT, but not different between CT-BG and CT-BP, ST and NT, or CT-BG and ST. Conventional tillage promoted N mineralization and plastic mulch increased soil temperature, which contributed to greater N2O-N fluxes. Though water filled porosity in NT was higher and correlated well with N2O-N fluxes, annual N2O-N emissions were lowest in NT suggesting a lack of substrates for nitrification and denitrification processes. Crop yield was lowest in NT in Year 1 and CT-BP in Year 3 but yield-scaled N2O-N emissions were consistently greatest in CT-BP and lowest in NT each year. Our results suggest that for coarse-textured soils in the coastal plain with winter cover crops, conservation tillage practices may reduce N2O emissions in organic vegetable production systems. [Display omitted] •Tillage effects on N2O emissions were evaluated jointly with winter cover crops in organic vegetable production system.•Conventional tillage [with black plastic mulch (CT-BP) or bare-ground (CT-BG)] increased soil temperature and mineral N.•Annual N2O emissions were lower in strip till (ST) and no till (NT) than in CT-BP and lower in NT than in CT-BG.•Vegetable yield was lowest in NT in year 1 and in CT-BP in year 3.•Yield-scaled N2O-N emissions were lower in NT and ST than in CT-BP.